Unveiling the melting dynamics of phase change material with geometrically configured porous copper inserts: Experimental and numerical analysis - Kiyak, Burak; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2025)
Experimental and numerical analysis have been performed in this study to investigate the partially embedded Phase Change Material (PCM) into copper plates bar with different configurations. ANSYS Fluent was used for numerical modelling. RT25HC, a paraffin-based PCM with a melting range of 22-26 degrees C, was tested in a rectangular box heated from the bottom. Six configurations of porous copper inserts were evaluated to enhance heat transfer (HT). Metal foam, chosen for its superior thermal conductivity, was utilized as a passive element to enhance heat transfer and control the melting process. It is found that Cases 1 and 2 reduced the PCM volume by 2.5 %, with Case 1 storing 6.2 % more energy and outperforming Case 2 (4.77 %) relative to the base case. Cases 3-6 reduced the volume by 1.5 %, with Case 5 achieving the highest increase at 5.7 %. This shows that the orientation, segmentation, and positioning of the porous structure embedded in PCM affect (HT) efficiency. The study systematically examines to control melting, HT and fluid flow by using six different configurations of copper porous inserts. This is the novelty of the work, which provides practical insights into the geometric design and optimization of latent heat thermal energy storage systems.
Keywords: PCM; Porous medium; Copper foam; Melting; Numerical analysis; Experimental